Gauging Distance Education Students’ Comfort Level With Technology and Perceptions of Self-Assessment and Technology Training Initiatives - Tracy Irani; Ricky Telg (Journal of Applied Communications, 2002)
Distance education has made great strides toward enfranchising nontraditional learners. Yet, while technology has continued to evolve and develop, student support services, especially those focused on technology training and assessment, are still a critical need. This study examined a representative sample of undergraduate, graduate, and postbaccalaureate agricultural students to determine the effect of demographics and prior distance education experience on their perceptions of the need for distance education assessment and training and their comfort level with distance learning technologies. Results indicated that respondents with previous distance education experience rated their comfort level with technology lower than those students taking a distance education course for the first time. A majority of respondents also said they would engage in technology training if their assessment indicated they needed technology skills.